HALL-EFFECT-CONTROLLED GAS DYNAMICS IN PROTOPLANETARY DISKS. I. WIND SOLUTIONS AT THE INNER DISK - Bai, Xue-Ning (The Astrophysical journal, 2014)
The gas dynamics of protoplanetary disks (PPDs) is largely controlled by non-ideal magnetohydrodynamic (MHD) effects including Ohmic resistivity, the Hall effect, and ambipolar diffusion. In this series, we have included, for the first time, all three non-ideal MHD effects in a self-consistent manner to investigate the role of the Hall effect on PPD gas dynamics using local shearing-box simulations. In this first paper, we focus on the inner region of PPDs, where previous studies (Bai & Stone 2013; Bai 2013) excluding the Hall effect have revealed that the inner disk up to ~10 AU is largely laminar, with accretion driven by a magnetocentrifugal wind. We confirm this basic picture and show that the Hall effect modifies the wind solutions depending on the polarity of the large-scale poloidal magnetic field B sub(0) threading the disk. Scaling relations for the wind properties, especially the wind-driven accretion rate, are provided for aligned and anti-aligned field geometries.